Analisis Biaya Volume Laba Sebagai Alat Perencanaan Laba Pada Cv Waringin Putih Semarang - Novan Yudi Cahyadi; Sulistiyo Sulistiyo (Jurnal Aktual Akuntansi Keuangan Bisnis Terapan (AKUNBISNIS), 2018)
This final project discusses how profit planning at CV Waringin Putih Semarang by applying the cost volume profit analysis. The purpose of this final project is to calculate the contribusion margin, break even point, profit planning in 2017, margin of safety, degree of operating leverage, and shut down point, and also to examine the asumpsions that affect profit at CV Waringin Putih Semarang with sensitivity analysis.The method of collecting data used in this final project is interviews, and documentation. The data used are secondary data obtained from CV Waringin Putih Semarang includes sales data, cost data, and general overview of the company. The writing of this final project used description method and exposition method. Description method used to describe the general overview of the company, while exposition method used to calculate the approaches that will be used to describe the cost volume profit analysis.Based on the cost volume profit analysis has been done, obtained the weighted average contribution margin of Rp20.638,73 per m2. Sales to break even point as much as 24.024 m2. Sales to reach the profit target increased by 17,21 %, or as much as 66.026 m2. Margin of safety is 63,62% and degree of operating leverage is about 1,74, and also sales to shut down point as much as 20.655 m2.